Sunken Efforts? Legal Hurdles to Stemming Maritime CBRNE Proliferation - Arjun Banerjee (International Journal of Nuclear Security, 2020)
For four centuries, the law of the sea has rested on the principle of mare liberum or the freedom of the high seas. The oceans have traditionally been regarded as areas over which no state could claim dominion or sovereignty. Nations desirous of countering security threats have found that their efforts are curtailed by the traditional paradigm, partly because of the resistance from other states to permit further derogation. Several extant laws aim to contain the spread of CBRN (chemical, biological, radiological and nuclear) material through a variety of measures. Certain bilateral agreements between nations exist, but the foreign vessel still tends to remain sacrosanct primarily because of the United Nations Convention on the Law of the Sea. Normally, merchant vessels in the open seas may only be stopped and searched without flag state consent in rare circumstances. In light of the scourge of a terrorist CBRN attack hanging like a Damocles’ sword upon the world today, this article seeks to discern whether a state possesses the right to interdict and search vessels of another state suspected of ferrying CBRN material in international waters. Countering the kind of faceless non-state actor threats of the 21st Century would require curtailing some of these freedoms earlier enjoyed in the open seas. Better integration of maritime laws, such as the relevant sections of the UNSCR 1540, the PSI and the SUA 2005 with the UNCLOS is of the essence.